QUALITY OF LIFE AND PSYCHOEMOTIONAL DISORDERS IN PATIENTS WITH MYASTHENIA - L. G. Zaslavskiy; A. B. Khurshilov; E. N. Skornyakova (Klinicist)
Objective. To assess the quality of life and mood disorders of patients with myasthenia gravis.Materials and methods. A comprehensive clinical and neuropsychological testing of 34 patients, accounting for 43.6 % of all patients with myasthenia living in the Leningrad region. To assess the severity of the international rating scale used by the severity of myasthenia gravis (MGFA). For the diagnosis of affective disorders, anxiety scale and Spielberger–Khanin depression scale, CES-D were used, quality of life was assessed by the SF-36 scale. The study included patients with stable clinical picture at least for the last 2 months. Comparison was made in population as well as within the studied group, divided into several groups depending on the severity and duration of the disease.Results. The quality of life of patients with myasthenia gravis in terms of physical health significantly lower (p = 0.04) than in the general population and directly depends on the severity of the disease. Depressive disorders are typical for patients with a long (more than 3 years) history of the disease, including the level of depression scale CES-D averaged 28.1 balls, which was significantly (p = 0.03) higher than for the patients in the early stages of the disease. In assessing affective disorders with anxiety scale Spielberger–Khanin was expressed by the average value on the scale of situational anxiety – 31.8 ± 8.3 points, and on the scale of personal anxiety 31.5 ± 8.1 points, indicating moderate anxiety disorder. We have not found a statistically significant relationship of affective disorders with disease severity and bulbar syndrome.Conclusion. The quality of life of patients with myasthenia generally reduced in comparison with the general population, and depending on the severity and depressive disorders typical for patients with a long history of the disease.